2003
DOI: 10.1002/ajpa.10267
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and antemortem tooth loss in the Northern Peten area, Mexico: A biocultural perspective on social status differences among the Classic Maya

Abstract: Dental caries and antemortem tooth loss (AMTL) are investigated in a Classic Maya sample obtained from the sites of Calakmul, Dzibanché, and Kohunlich (Mexico). This study aims at assessing the effect that sex and social status had on the prevalence of oral pathologies. The lack of a direct relationship between caries, AMTL, and age-at-death led us to interpret the results in terms of the biological, socioeconomic, and behavioral conditions prevailing in these ancient Maya settlements. Benefits related to sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 23 publications
5
62
1
3
Order By: Relevance
“…Similar results were found in Belize (White 1994), where higher-class individuals had significantly lower caries rates than the lower classes, likely indicating greater access to animal proteins rather than a diet based upon maize. In contrast, Cucina and Tiesler (2003) noted that among the Classic Maya, people of higher social status likely had easier access to cariogenic foods. Further, in Swärdstedt's (1966) work on Medieval Swedish remains, the low-, middle-, and upper-class individuals showed no significant difference in dental caries rates, implying that individuals were eating a similar diet regardless of social rank.…”
Section: Discussionmentioning
confidence: 89%
“…Similar results were found in Belize (White 1994), where higher-class individuals had significantly lower caries rates than the lower classes, likely indicating greater access to animal proteins rather than a diet based upon maize. In contrast, Cucina and Tiesler (2003) noted that among the Classic Maya, people of higher social status likely had easier access to cariogenic foods. Further, in Swärdstedt's (1966) work on Medieval Swedish remains, the low-, middle-, and upper-class individuals showed no significant difference in dental caries rates, implying that individuals were eating a similar diet regardless of social rank.…”
Section: Discussionmentioning
confidence: 89%
“…AMTL results from many causes, including dental caries, periodontal disease, attrition, trauma, and ritual tooth extraction; however, it has been suggested that AMTL is often caused by dental caries (Sakura, 1964;Lukacs, 1995;Hillson, 2001;Cucina and Tiesler, 2003;Palubeckaite et al, 2006;Oyamada et al, 2007a). In the case of Kumejima, a tradition of ritual tooth extraction did not exist and no large battles took place in the early-modern times that may have resulted in trauma-related tooth loss (Nakahara, 1990;Doi, 2003;Uezu, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of dental caries and antemortem tooth loss in the northern Petén area of Mexico documented differences in frequency by social status (Cucina & Tiesler, 2003).…”
Section: Dietary Variations and Amtlmentioning
confidence: 99%